PERFORMA LINGKUNGAN DAN DERAJAT PENYAJIAN INFORMASI LINGKUNGAN PERUSAHAAN NON KEUANGAN DI INDONESIA - Alwan Sri Kustono (Universitas Muhammadiyah Jember, 2020)
The purpose of this study was to examine the effect of environmental performance factor on corporate social responsibility disclosure. Firm size, profitability, and company debt as control variables. CSR disclosure as the dependent variable is proxied by the GRI index. The research sample is the annual reports of non-financial companies that have participated in the Proper program and have been listed on the IDX 2014-2018. There are 55 companies that fillful the sample criteria with 275 firm years. Methods of data analysis using multiple regression. The test results show that the company's environmental performance has a positive and significant effect on the level of corporate environmental disclosure in the annual report. The positive value possessed by the environmental performance variable of the company shows that the environmental performance carried out by the company is in the same direction (direction) as the company's environmental disclosure. The better the company's performance in environmental performance, the higher the company's environmental disclosure level in the published annual report. This condition is in accordance with the signal theory that companies tend to disclose the company's environmental performance to maintain or enhance the company's image among pemangku kepentingans. Environmental performance and disclosures that are made are a form of company responsibility towards pemangku kepentingan demands and to maintain company legitimacy and avoid legitimacy conflicts. Corporate social responsibility is essential to ensure the continuity of today's business world. The company not only has obligations to shareholders, but more to pemangku kepentingans.